Molecular Basis Underlying Hepatobiliary and Renal Excretion of Phenolic Acids of Salvia miltiorrhiza Roots (Danshen) - Lu, Jun-Lan; Zeng, Xue-Shan; Zhou, Xin; Yang, Jun-Ling; Ren, Ling-Ling; Long, Xin-Yu; Wang, Feng-Qing; Olaleye, Olajide E.; Tian, Nan-Nan; Zhu, Ya-Xuan; Dong, Jia-Jia; Jia, Wei-Wei; et al. (Frontiers in Pharmacology, 2022)
Phenolic acids are cardiovascular constituents (originating from the Chinese medicinal herb Salvia miltiorrhiza root/Danshen) of DanHong and many other Danshen-containing injections. Our earlier pharmacokinetic investigation of DanHong suggested that hepatic and/or renal uptake of the Danshen compounds was the crucial steps in their systemic elimination. This investigation was designed to survey the molecular basis underlying hepatobiliary and renal excretion of the Danshen compounds, i.e., protocatechuic acid, tanshinol, rosmarinic acid, salvianolic acid D, salvianolic acid A, lithospermic acid, and salvianolic acid B. A large battery of human hepatic and renal transporters were screened for transporting the Danshen compounds and then characterized for the uptake kinetics and also compared with associated rat transporters. The samples were analyzed by liquid chromatography/mass spectrometry. Because the Danshen phenolic acids are of poor or fairly good membrane permeability, their elimination via the liver or kidneys necessitates transporter-mediated hepatic or renal uptake from blood. Several human transporters were found to mediate hepatic and/or renal uptake of the Danshen compounds in a compound-molecular-mass-related manner. Lithospermic acid and salvianolic acid B (both > 500 Da) underwent systemic elimination, initiated by organic anion-transporting polypeptide (OATP)1B1/OATP1B3-mediated hepatic uptake. Rosmarinic acid and salvianolic acids D (350–450 Da) underwent systemic elimination, initiated by OATP1B1/OATP1B3/organic anion transporter (OAT)2-mediated hepatic uptake and by OAT1/OAT2-mediated renal uptake. Protocatechuic acid and tanshinol (both < 200 Da) underwent systemic elimination, initiated by OAT1/OAT2-mediated renal uptake and OAT2-mediated hepatic uptake. A similar scenario was observed with the rat orthologs. The investigation findings advance our understanding of the disposition of the Danshen phenolic acids and could facilitate pharmacokinetic research on other Danshen-containing injections.